FEATURES OF THE COURSE OF CHRONIC RECURRENT APHTHOUS STOMATITIS IN WOMEN OF FERTILE AGE - Navruzova Ugilkhon Orzizhonovna (TADQIQOTLAR.UZ, 2024)
ANNOTATION. Distribution and clinical function according to chronic recurrent aphthous stomatitis in pregnant women, most less Learned the same. at that time, the mouth is the primacy of the mucus floor inflammation of the fetus internal infectious disease and complication development due to Dangerous is considered chronic recurring aphthous stomatitis morphological elements mucus floor desired in place is located, but the most favorite places are the lips, cheeks, lateral surface of the tongue and the transition of the fold into the field of mucus this is the floor. The wounds are usually round, be and leak, fibrinosis cover with a covered Chronic recurrent aphthous stomatitis, as well as the etiology and pathogenesis have not been fully studied, each as a disease, care is a difficult task. This is why for every single patient, individual local and general nursing care measures will be used.